Cloning, nucleotide sequence, and regulation of the Bacillus subtilis pbpF gene, which codes for a putative class A high-molecular-weight penicillin-binding protein. - Popham, D L (1993)
The partial nucleotide sequence of a gene encoding a Bacillus subtilis homolog to the Escherichia coli ponA gene, encoding penicillin-binding protein 1A, was previously reported. The remaining part of this gene, termed pbpF, was isolated, and its nucleotide sequence was completed. Deletion of this gene did not alter the profile of B. subtilis penicillin-binding proteins observed after gel electrophoresis and resulted in no observable phenotype. A transcriptional pbpF-lacZ fusion was weakly expressed during vegetative growth. Expression diminished during the first hours of sporulation but was slightly induced in the forespore compartment during late sporulation. This sporulation expression was dependent on spoIIIG, which encodes the forespore-specific transcription factor sigma G. A single transcription start site which was apparently directly dependent on E sigma A was detected in vegetative cells.